Atmospheric moisture in the Arctic and Antarctic - Naakka, Tuomas (Helsingin yliopisto, 2022)
Water vapour is an effective greenhouse gas, but clouds, which are formed when water vapour condenses into water droplets or ice crystals, may have an even greater effect on radiative energy transfer through the atmosphere. In addition, absorption or release of the latent heat of vaporization and transport of water vapour are part of the heat transport from the Tropics towards the Poles. Thus, atmospheric water vapour greatly affects the energy balance of the atmosphere and is also an important component of the water cycle. This thesis addresses the subject of atmospheric moisture and the processes affecting it in the Arctic and Antarctic. The studies comprising the thesis are mostly based on atmospheric reanalyses. In the polar regions, meteorological observation networks are sparse, due to their remoteness and the harsh environment, and therefore traditional observations have not provided a comprehensive picture of atmospheric conditions in the polar regions. In recent years, atmospheric reanalyses have also become more accurate in remote areas, which has enabled detailed studies of atmospheric moisture in the polar regions. In the polar regions, the mostly negative radiation budget of Earth’s atmosphere-surface system shapes the distribution of water vapour in the atmosphere, especially the vertical structure of specific humidity. The polar regions are sinks for atmospheric water vapour, due to their typically small local evaporation, and even condensation of moisture on the surface. Therefore, moisture transport from the lower latitudes balances the moisture budget in the polar regions. This type of moisture budget favours the formation of specific humidity inversions. Our results show that specific humidity inversions are common in the polar regions, and their occurrence near Earth’s surface is linked with surface conditions: radiative surface cooling, occurrence of temperature inversions in winter and cold sea surfaces or melting of sea ice in summer. Advection of warm, moist air masses over a cold surface ...